Organic markers and OC source apportionment for seasonal variations of PM2.5 at 5 rural sites in France. (1st February 2019) - Golly, B.; Waked, A.; Weber, S.; Samake, A.; Jacob, V.; Conil, S.; Rangognio, J.; Chrétien, E.; Vagnot, M.-P.; Robic, P.-Y.; Besombes, J.-L.; Jaffrezo, J.-L.
Abstract: The chemical characterization of PM2.5 was conducted at 5 rural background sites in France for the year 2013. Chemical analysis of daily samples every sixth day included the measurements of organic carbon (OC), elemental carbon (EC), ionic species and several specific primary and secondary organic tracers such as levoglucosan, polyols, methane sulfonic acid (MSA) and oxalate. The sampling sites were spatially distributed in order to be representative of the French atmospheric background. The results showed well identified temporal variations common to all the 5 sampling sites, covering a large fraction of France. During winter, concentrations of the biomass burning marker levoglucosan are significantly increased with high synchronous temporal pattern, indicating the strong impact of this source at a regional scale. During summer, concentrations of primary biogenic markers such as polyols (arabitol, mannitol) increase due to higher biological activities while oxalate contributions to OC also increases, attributed to ageing processes. The sources of primary organic aerosol are investigated using mono-tracer approaches based on these compounds. Results indicate that the relative contributions of wood burning to OC are very high, reaching an average value of 90% during winter for some of the rural sites. Terrestrial primary biogenic organic fraction is significant in summer and fall with a monthly contribution ranging from 4.5 to 9.5% of OC in PM2.5 . A synchronous increase is also observed for secondary organic tracers (MSA, oxalic acid) during warm period confirming the influence on the large scale of these compounds that can account for 10–20% and 5–7% of the OC mass, respectively. Highlights: Annual chemical composition and seasonal variability of rural PM2.5. Synchronous variability of primary and secondary organic compounds. OC source apportionment using primary molecular markers. 30% of the total OC attributed to the fungal spore during harvesting periods. PSCF analysis highlighted a potential terrestrial additional source of MSA in continental sites.